Effects of capsaicin on pharmacokinetics of pitavastatin in rats. (February 2015) - Chen, Fen; Zhai, Xuejia; Zhu, Chaoran; Lu, Yongning
Abstract 1. Capsaicin (CAP) is the primary pungent principle in peppers and an inhibitor of CYP3A subfamily and P-gp. 2. Pitavastatin is mainly metabolized via glucuronidation and metabolism by hepatic CYPs is minimal. Pitavastatin is taken up by Oatp1b2 (encoded by Slco1b2) in rat. 3. The pharmacokinetics results showed that AUC and Cmax in the group pre-treated with 3 mg/kg/d CAP were increased by 1.2 fold and 1.6 fold; AUC and Cmax in the group pre-treated with 8 mg/kg/d CAP were increased by 2.1 fold (p < 0.05) and 2.9 fold (p < 0.05); AUC and Cmax in the group pre-treated with 25 mg/kg/d CAP were increased by 2.0 fold and 1.9 fold. The RT-PCR data indicated that pretreatment with CAP had little influence on the mRNA expression level of Slco1b2 in liver. These results demonstrated that chronic ingestion of CAP increases the bioavailability of pitavastatin in rat and that Oatp1b2 gene expression in rat liver is hardly effected by CAP.